Perlindungan Hukum Pemilik Merek Terhadap Penyalahgunaan Nama Domain: Perbandingan Amerika Dengan Indonesia - Sindhy Wahyu Dwi Agustin (Fakultas Hukum, 2026)
Legal Protection of Trademark Owners Against Domain Name Abuse: A Comparison Between the United States and Indonesia; Sindhy Wahyu Dwi Agustin; 220710101002; 2026; 61 Pages; Law Study Program, Faculty of Law, University of Jember. Advances in information technology have driven the transformation of commerce into the digital realm, including the use of trademarks as business identities. Trademarks serve as a key differentiator in competition and have now expanded to include the use of domain names as digital identities. Initially, domains were merely technical addresses, but they have evolved into strategic assets tied to reputation and economic value. Legally, domains and trademarks are governed by different legal frameworks in Indonesia. The ITE Law applies the first-come-first-served principle, without explicit provisions regarding trademark protection in domain registration. The Trademark Law also has not yet addressed this issue. Consequently, a regulatory gap has emerged, creating opportunities for domain abuse by unauthorized parties, harming trademark owners and consumers. Cases such as bmw.id and netflix.id illustrate this problem. Unlike Indonesia, the United States has established regulations through the ACPA, which provides explicit protection. Therefore, specific regulations are needed in Indonesia to address domain abuse. The research method employed is legal research. The research questions in this thesis are: What is the urgency of domain name regulation in trademark protection? What forms of legal protection do trademark owners have against domain name misuse? And what should future regulations regarding domain names in Indonesia look like? The general objective of this study is to analyze and compare the legal protections available to trademark owners against domain name misuse in the United States and Indonesia. Specifically, this study aims to analyze the urgency of domain name regulation in trademark protection, understand the forms of legal protection for trademark owners against domain name misuse, and provide recommendations for future domain name regulation in Indonesia based on the rules applied in the United States. The theoretical benefits of this study are that it is expected to contribute to the development of legal science, particularly regarding trademark protection and domain name regulation. Practically, the results of this research can serve as a reference for policymakers, law enforcement officials, and business actors in handling domain name and trademark disputes, as well as provide a basis for policymakers in drafting or revising domain name regulations in Indonesia. The research method used in this thesis is legal research employing a statutory, conceptual, and comparative legal approach. The data used consists of primary legal sources such as laws and regulations, as well as secondary legal sources such as books, theses, and legal journals. Data collection was conducted through a literature review. The data was analyzed by comparing the regulations applied by the two countries. This involved examining and reviewing various relevant literature, theories, and previous research findings related to the research topic. Through several studies, namely an Overview of DIGITAL REPOSITORY UNIVERSITAS JEMBER DIGITAL REPOSITORY UNIVERSITAS JEMBER xv Intellectual Property Rights, which covers the definition of Intellectual Property Rights and the Scope of Intellectual Property Rights, followed by an Overview of Trademarks, which covers the Definition of Trademarks, Types of Trademarks, Benefits and Functions of Trademarks, and the Trademark Registration System, the Purpose of Trademark Protection, the Duration of Trademark Protection, and a General Overview of Domain Names, which covers the Definition of Domain Names, the Functions of Domain Names, Rules Regarding Domain Names, as well as a General Overview of Cybersquatting, which covers the Definition of Cybersquatting, Forms and Modes of Cybersquatting, so that the researcher can understand existing concepts and ideas to analyze the research problem. Research findings indicate that domain name regulation has become urgent because the growth of the digital economy has made domains a brand identity with economic value that is vulnerable to abuse through cybersquatting. The difference in registration principles between domains (first come, first served) and trademarks (first to file) has led to legal conflicts in Indonesia. Legal protection is already available through the Trademark Law, the ITE Law, and dispute resolution mechanisms such as the UDRP; however, it remains suboptimal due to a lack of integration. This contrasts with the United States, which has established clear regulations through the Anti-Cybersquatting Consumer Protection Act (ACPA). Therefore, Indonesia needs to adopt an approach similar to that of the United States by strengthening regulations and integrating domain names into trademark protection. Conclusions of this study: Domain names play a crucial role as brand identities in the digital age and are vulnerable to misuse. Legal protection in Indonesia remains suboptimal due to regulatory limitations and the lack of integration between the domain and trademark regimes. Research recommendations: Indonesia needs to revise the Trademark Law by integrating domain names, clarifying bad-faith provisions, strengthening inter-agency coordination, and adopting an approach similar to the ACPA.
Validasi dan Finalisasi oleh Ratna 9 Juni 2026
Keywords: Domain; Brand; Legal protection